KECAKAPAN SISWA BERMATEMATIKA MELALUI PENGUATAN PENDIDIKAN KARAKTER ABAD 21 - Hartadi Gatot (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2018)
Mathematics is one of the subjects that is unique in terms of problem solving. This is based on solving problems related to mathematics can be passed in various ways. This requires a spirit of creativity so that students can develop themselves into creative and innovative people in solving problems. In the learning process, teachers can use innovative learning approaches, strategies, models, or methods in the form of problem-based learning, one of the learning that reflects 21st century learning is PBL4C, is one of the innovative learning models that can provide learning conditions independently to students by directing students to work together (mutual cooperation) to solve a problem and of course the end result of this learning students are able to represent a work related to various problems in Mathematics. The application of PBL4C instructional activities is based on learning strategies involving semantic reasoning, case-based reasoning, analogical reasoning, causal reasoning, and inquiry reasoning. There are five phases of the implementation of problem-based learning, namely (1) orienting students to problems, (2) organizing students to learn, (3) guiding individual or group investigations, (4) developing and presenting work and (5) analyzing and evaluating processes solution the problem.